Regioselective Synthesis of Trisubstituted Quinoxalines Mediated by Hypervalent Iodine Reagents - Suzuki, Yumiko; Takehara, Ren; Miura, Kasumi; Ito, Ryota; Suzuki, Noriyuki (Journal of organic chemistry, 2021)
A facile and regioselective synthesis of quinoxalines, an important motif in medicinal chemistry and materials sciences, was developed. Despite their prospective utility, the regioselective preparation of trisubstituted quinoxalines has not been previously established. In the reported system, hypervalent iodine reagents catalyzed the annulation between α-iminoethanones and o-phenylenediamines in a chemo/regioselective manner to afford trisubstituted quinoxalines. Excellent regioselectivities (6:1 to 1:0) were achieved using [bis(trifluoroacetoxy)iodo]benzene and [bis(trifluoroacetoxy)iodo]pentafluorobenzene as annulation catalysts.